2012
DOI: 10.1111/j.1469-8137.2011.04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic changes in ectomycorrhizal community composition, root tip abundance and mycelial production along a stand‐scale nitrogen deposition gradient

Abstract: Summary• Nitrogen (N) availability is known to influence ectomycorrhizal fungal components, such as fungal community composition, biomass of root tips and production of mycelia, but effects have never been demonstrated within the same forest.• We measured concurrently the abundance of ectomycorrhizal root tips and the production of external mycelia, and explored the changes in the ectomycorrhizal community composition, across a stand-scale N deposition gradient (from 27 to 43 kg N ha) at the edge of a spruce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 46 publications
12
106
2
2
Order By: Relevance
“…Another key driver of EMF community composition is nitrogen (NO 3 À , NH 4 þ ) availability, as shown in temperate and boreal forests (e.g., Toljander et al 2006, Kjoller et al 2012 as well as in bacterial and fungal communities in Antarctic soils (Yergeau et al 2007). Nitrate and NH 4 þ increased from subzone A to D and were correlated with EMF community structure, extending the patterns seen in previous studies in the Arctic.…”
Section: Factors Shaping Emf Communitiesmentioning
confidence: 99%
“…Another key driver of EMF community composition is nitrogen (NO 3 À , NH 4 þ ) availability, as shown in temperate and boreal forests (e.g., Toljander et al 2006, Kjoller et al 2012 as well as in bacterial and fungal communities in Antarctic soils (Yergeau et al 2007). Nitrate and NH 4 þ increased from subzone A to D and were correlated with EMF community structure, extending the patterns seen in previous studies in the Arctic.…”
Section: Factors Shaping Emf Communitiesmentioning
confidence: 99%
“…Furthermore, both fine-root architectural and morphological traits may vary as a consequence of interactions with soil biota, such as ectomycorrhizal fungi, which may confound plastic root responses to resource availability (Freschet et al 2015). On poor soils for example, ectomycorrhizal mycelium biomass increases (Nilsson et al 2005;Kjøller et al 2012;Bahr et al 2013), which enlarges the soil volume available to the plant (Smith and Read 2008), and therefore possibly reduces the need for fine-root architectural or morphological adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…Ectomycorrhizal communities are usually composed of a diverse flora consisting of several dominant and many infrequent EMF species (Buée et al, 2007;Courty et al, 2010;Pena et al, 2010;Tedersoo et al, 2012a;Danielsen et al, 2013). EMF community structures are strongly influenced by N deposition (Lilleskov et al, 2011;Kjøller et al, 2012). Stable isotope studies have revealed that EMF species differ in their abilities to exploit different N sources (Hobbie and Hö gberg, 2012).…”
Section: Introductionmentioning
confidence: 99%